A Persian version of Geriatric Oral Health Assessment Index. (15th October 2014) - Rezaei, Mohammad; Rashedi, Vahid; Khedmati Morasae, Esmaeil
Abstract : Objective: This study aimed to translate the original English version of the Geriatric Oral Health Assessment Index (GOHAI) into a Persian version and to assess the preliminary psychometric properties of the translated index among a sample of Persian elders. Material and methods: Twelve items included in GOHAI were first translated into Persian using a back‐translation technique and then were compared with the original version. Four hundred and seventeen elderly subjects who were admitted to a day care centre answered GOHAI and an attached socio‐demographic questionnaire. Internal consistency of the Persian version was measured by Cronbach's alpha. Test–retest reliability was assessed by intraclass correlation coefficient (ICC) and weighted kappa. Factor structure of GOHAI was evaluated by principal component factor analysis. Results: Mean of GOHAI score was 45.71 (SD: 5.14; range: 27–51). The mean of GOHAI score was higher for the elders who rated their oral and general health as 'good'. The Cronbach's alpha for GOHAI score was 0.748, indicating a high degree of internal consistency and homogeneity between the GOHAI items. The test–retest correlation for the total GOHAI score using ICC was 0.763 (95% CI = 0.713–0.809). Factor analysis revealed a three‐factor solution that bolstered the theoretical construction of the index. Significant differences in the GOHAI scores were found for income and current number of teeth. Conclusion: The Persian version of the GOHAI can be used reliably to identify oral health‐related concerns of older Persian speakers, but further research is needed to confirm its cultural consonance in this population.